ASEAN and Great Power Rivalry in Regionalism: From East Asia to the Indo-Pacific - Yoshimatsu, Hidetaka (Journal of Current Southeast Asian Affairs, 2023)
The Association of Southeast Asian Nations (ASEAN), which serves as the linchpin of regionalism in East Asia, is facing a new challenge of great power politics. This article explores ASEAN's position in and strategy for taking cooperative regional initiatives by referring to the management of confrontational politics between rival states. It explains ASEAN's handling of great power politics theoretically by impartial enmeshment for managing great powers’ material interests and moral legitimacy in developing specific ideational frameworks. This article argues that ASEAN managed great powers’ rivalry by enmeshing them into its regional initiatives impartially and maintaining organisational legitimacy by developing systems of socio-cultural norms. It also contends that ASEAN needs, in envisioning the future of Indo-Pacific regionalism, to extend its strategic reach through alignments with other parties and enhance moral legitimacy by deepening and broadening normative frameworks for advancing collective interests for the Indo-Pacific region.